G479(P) Study to find out the prevelance of vitamin d deficiency in cord blood. (24th May 2017) - Vij, V; Gupta, V; Balan, S; Kaul, S
Abstract : Background: In a country like ours where sunshine is abundant throughout the year, the magnitude of vitamin D deficiency is still huge. In India studies have reported deficiency levels ranging from 50%–86.5% for newborns and young infants. There remains considerable debate over the serum concentrations of 25 (OH) D associated with optimal health, and cut-off points have not been developed by a scientific consensus process. Till date specific range for neonates is not available. Aims: This study was thereby undertaken to know the status of vitamin D in cord blood and to find out the prevalence of its deficiency and to determine whether deficiency affects the anthropometric parameters of the newborn. Materials and methods This cross sectional study was conducted from October 2013 to April 2014, where consecutive 255 singleton newborns of all gestation age delivered were enrolled. Approximately 4 ml of umbilical cord venous blood was obtained and sent for estimation of vitamin D levels. Anthropometry measurements of the baby were taken including birth weight, head circumference and length. A correlation analysis was performed using the Pearson's correlation test with logarithmic transformations where necessary. Results: 73.3% of the cord samples were deficient (<20 ng/ml) in Vitamin D, with severe deficiency (<10 ng/ml) seen in 49% of the samples. Birth weight was significantly higher (2.99±0.57 kg) in babies having normal cord vitamin D level. Conclusion: Vitamin D deficiency is very common in Indian newborns. Efforts to assess and treat vitamin D deficiency during pregnancy and provide adequate supplementation to newborns are necessary to rectify such a serious public health concern.